2009
DOI: 10.1051/radiopro/20095039
|View full text |Cite
|
Sign up to set email alerts
|

Induction of oxidative stress related responses inArabidopsis thalianafollowing uranium exposure

Abstract: Abstract. The reactive oxygen species (ROS)-signaling pathway is very important in heavy metal toxicity. Induction of the antioxidative defense mechanism, comprising ROS-scavenging enzymes and metabolites, in plants after environmental uranium contamination has been insufficiently studied in the past. This study aimed to analyze oxidative stress related responses in Arabidopsis thaliana after uranium exposure. Seventeen-day-old seedlings were exposed to 0, 0.1, 1, 10 and 100 M uranium for 3 days. After exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…With different localizations (cytosol (Cu/ Zn SOD), plastids (Fe SOD), and mitochondria (Mn SOD)), the enzyme has different expressions not only in the plant cell but depending also on the site of U action. For example, Vanhoudt et al (2009) showed that SOD from cytosol provides a weak antioxidant action and that in roots plastids exhibits an improved antioxidant defense, which is not the case of leaf plastids; meanwhile, mitochondrial SOD easily copes with exposure to U. Our investigation focused on total SOD activity and is possible that one of the isoforms was strongly activated, while others were inhibited, which also explains the variation of SOD activity between the exposed species.…”
Section: Biochemical Observationsmentioning
confidence: 87%
See 2 more Smart Citations
“…With different localizations (cytosol (Cu/ Zn SOD), plastids (Fe SOD), and mitochondria (Mn SOD)), the enzyme has different expressions not only in the plant cell but depending also on the site of U action. For example, Vanhoudt et al (2009) showed that SOD from cytosol provides a weak antioxidant action and that in roots plastids exhibits an improved antioxidant defense, which is not the case of leaf plastids; meanwhile, mitochondrial SOD easily copes with exposure to U. Our investigation focused on total SOD activity and is possible that one of the isoforms was strongly activated, while others were inhibited, which also explains the variation of SOD activity between the exposed species.…”
Section: Biochemical Observationsmentioning
confidence: 87%
“…It should be taken into account that the enzymes are proteins and that a significant increase in leaf soluble protein concentration due to the accumulation of U in the soil was previously recorded (Shtangeeva et al, 2006). Vanhoudt et al (2009) stated that the level of antioxidant enzyme activity at the cellular level, activated by the presence of U in the environment, does not decrease when compared to the soluble proteins. These observations can be used also as significant elements that show the degree of soil pollution.…”
Section: Biochemical Observationsmentioning
confidence: 99%
See 1 more Smart Citation